Effect of Shuttlecock Throwing Exercise to Increase Power Arm Lob Punch in Badminton Players Aged 7-9 Years - Zuhriyah, Faizatuz; Aliriad, Hilmy; Cahyani, Olivia Dwi; Ramadhan, Nurman; Da'i, Mohamad (MultiTech Publisher, 2023)
Badminton players aged 7-9 years still have difficulty in making lob shots, which are lob shots that do not bounce and tend to be tolerant. To overcome this, can be given a shuttlecock throwing exercise. This study aims to determine the effect of shuttlecock throwing style to increase arm strength in lob badminton players aged 7-9 years in PB. Angkor Kusuma Bojonegoro.This type of research is an experiment with a